Periocular Myxoma in a Child - Dolores Ríos y Valles-Valles; Ana María Vera-Torres; Héctor A. Rodríguez-Martínez; Abelardo A. Rodríguez-Reyes (Case Reports in Ophthalmological Medicine)
Myxomas are locally invasive, benign mesenchymal neoplasms with odontogenic, osteogenic, or soft tissue origin. Facial myxomas probably account for less than 0.5% of all paranasal sinus and nasal tumors. We report a case of a left painless periocular mass in a 11-month-old girl. The lesion was resected with a clinical diagnosis of lacrimal sac tumor. Histopathology and immunohistochemistry proved the tumor to be a myxoma. There has been no recurrence after 4 years of followup. Midfacial myxomas should be differentiated from other benign and malignant tumors such as dermoid, hamartoma, neurofibroma, nasolacrimal duct cyst, and sarcomas in particular embryonal rhabdomyosarcoma. Because of the infiltrative nature of these tumors, a wide surgery is required to achieve clear resection margins and avoid recurrence.